The "Aero-Position": Why cyclists study aerodynamics (Illumin, 2020)
Greg LeMond`s 1989 Tour de France victory, aided by research-driven cycling advancements, marked the beginning of the open integration of aerodynamics into cycling. Eventually, progress in body positioning techniques, bicycle componentry, safety equipment and apparel led to the development of an optimal aerodynamic cycling stance known as the "Aero-Position." The aero-position is possibly the greatest advancement in cycling over the past 30 years. No other changes have produced the polarizing results that the aero-position brought about. It significantly increased speeds of cyclists and showed non-technical people that engineering has a place in sport.